Cultura financiera y toma de decisiones financieras en los microempresarios de la ciudad de Requena 2023 - Gomez Cabrera, Segundo Lucio (2025)
The general objective of this study was to determine the relationship between financial culture and financial decision-making in microentrepreneurs in the city of Requena, 2023. To achieve this objective, a descriptive level applied research was carried out, using a correlational approach with a non experimental and cross-sectional design. The study population consisted of 248 microentrepreneurs. Techniques such as surveys and questionnaires were used for this purpose. Finally, it was concluded that financial culture is rated as high, with 31%. This is because most microentrepreneurs usually have a bank card. In addition, they have the habit of keeping regular control of their expenses, either weekly or biweekly. For their part, financial decision making is adequate in 50%. This is because for the most part they assume financial risks taking into account the expected profitability and use tools or methods to evaluate such risks before making decisions. Overall, a correlation coefficient of 0.525 was identified, indicating a moderate correlation between financial literacy and the ability to make effective financial decisions in microentrepreneurs. In addition, the significance obtained of 0.000 allows us to conclude that the observed relationship is statistically significant. Keywords: Financial literacy, Decision making.